PEMBANGKIT LISTRIK TENAGA HIBRID SEBAGAI SOLUSI KELISTRIKAN DI DAERAH TERPENCIL - nurrohim, agus (Badan Pengkajian dan Penerapan Teknologi, 2012)
In order to meet electricity demand, the role of Diesel Power Generation (PLTD) in parts of Indonesia is still very large. Currently, 34.30% of electricity demand in outside of Java-Bali system was supplied by the PLTD. Especially for the Eastern Indonesia (Nusa Tenggara, Maluku, and Papua), nearly 100% of its electricity comes from PLTD. For the next 10 years, the government planning through PT. PLN will install 252 MW of PLTD in Eastern Indonesia and 73 MW in Western Indonesia. Due to the increasing of oil prices in the world will directly increase the oil prices in Indonesia, so that the electricity generating cost from PLTD would alsoincrease. To reduce fuel consumption without reducing the service to the consumer, the construction of Diesel Power Generation should be integrated with renewable energy, like Solar Power and Wind Power to form the Hybrid Power Generation. By the Hybrid Power Generation, energy management can be controlled, so the using of diesel fuel can be more efficient. By applying of Solar Power and Wind Power in a quarter of the capacity of PLTD, the consumption of fuel could be reduced by 152million liters up to 2019, or an average of 15.2 million liters per year.